Correlational Study of Peer Influence and Juvenile Delinquency among Secondary School Adolescents in Ibadan Metropolis / Adekola Kamil Lasisi, Adeseko Sunday Olaifa , Mutiu Ayofe Alabi - Lasisi, Adekola Kamil; Olaifa, Adeseko Sunday; Alabi, Mutiu Ayofe (2021)
A connection between peer-influence and adolescent delinquence among auxiliary school young people in Ibadan Metropolis was investigated. Multi-stage purposive sampling was used to select 120 participants. They consisted of 68 male and 42 female respondents with ages ranged between 11 and 18 years. The mean age and standard deviation of the ages are respectively 14.62 years and 13.37. Three research hypotheses were tested at 0.05 critical region. Two instruments were used to collect the data: Juvenile Delinquency Scale (r= 0.83) and Negative Peer Influence Scale (r = 0.95). The data collected were exposed to P. P. M. C. The findings showed that there was significant association between peer -influence and adolescent delinquency of the participants in Ibadan Metropolis (r. calculated = 0.54; df = 238; P < 0.05). It was observed that there was significant association between peer influence and delinquency of male secondary school adolescents in Ibadan Metropolis (r. calculated = 0.35; df = 134; P < 0.05); and that there was significant association between peer-influence and juvenile delinquency among female secondary school adolescents in Ibadan Metropolis (r. calculated = 0.27; df = 80; P < 0.05). The findings were discussed and necessary recommendations were put forward.